ผลของโปรแกรมส่งเสริมการรับรู้สมรรถนะแห่งตนต่อพฤติกรรมการดูแลของมารดา ในการป้องกันการกลับเป็นซ้ำของโรคปอดอักเสบในบุตรปฐมวัย - ยศรวีร์ กีรติภควัต (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this quasi-experimental research were to investigate maternal caring behavior to prevent recurrent pneumonia and examine the effect of perceived self-efficacy promoting program on maternal caring behavior to prevent recurrent pneumonia in toddler. The perceived self-efficacy theory (Bandura, 1997). The participans were mothers of toddler with pneumonia. Subjects were assigned to control group first,then experimental group, 20 per each. Groups were matched by age and educational level. The experimental group received the perceived self-efficacy promoting program,and the control group received routine nursing care. The intervention developed by a researcher consisted of 5 steps: 1) rapport building and prepare mother 2) health education providing 3) enhancing appropriate behavior 4) repeat skill practice 5) follow up. Materials used in the program included handbook and vcd developed by researcher. The intervention was reviewed for content validity by a panel of experts. Perceived self-efficacy was measured to monitor intervention effect. Its Cronbach s alpha coefficient was .85. The maternal caring behaviors questionnaire was used to collect the data. It demonstrated acceptable reliability with Cronbach s alpha was .87. Data were analyzed using descriptive statistics and dependent t-test. Major findings were as follows : maternal caring behavior to prevent recurrent pneumonia in toddler with the hightest score was "bringing children for vaccination as schedule". Maternal caring behavior to prevent recurrent pneumonia in the experimental group participating the perceived self-efficacy promoting program was significantly higher than those of the control group (p<.05).